Condicionamento físico e nutricional para o crescimento de plantas em solo afetado por rejeito de mineração de ferro - Borges, Pedro Henrique de Castro (2022)
In 2015, after the failure of the Fundão dam in Mariana – MG, the soils on the banks of the Doce River and its affluents were drastically altered by the deposition of iron ore tailings sludge. The substrate generated by the soil-tailing mixture was considered, at first, highly restrictive to plant development, due to its absent or poorly developed structure, low porosity, chemical restriction in the availability of essential nutrients for plant nutrition, low levels of organic matter, alkaline pH , among other factors. Due to the restrictions of the substrate composed of the soil-tailings mixture, this work was conceived with the objective of evaluating the growth of plants in the soil-tailings under the use of soil conditioners, fertilizers and physical modification by pelleting. For this, 4 experiments were carried out with the application of different levels of conditioners: sand, vermiculite, sawdust and organic compost. In these experiments, the indicator plant used was Cynodon spp., cultivar Tifton 85. Another 3 experiments were carried out to evaluate the effect of fertilization and physical modification by pelleting the tailings soil, using eucalyptus, brachiaria and beans as indicator plants. The results obtained showed that despite the use of conditioners and physical modification by pelleting, the plants under study showed adequate growth in the tailings soil as a function of the nutritional supply by the fertilization of the substrate. The use of plants such as brachiaria, eucalyptus and Tifton 85, which have an expressive biomass growth, can be used as the very method of conditioning and improving the soil-tailings in programs for the recovery of areas degraded by the deposition of iron mining tailings.